Redistribution and Non-Consumption Smoothing in an Open Economy - Perotti, Roberto (Review of Economic Studies, 1996)
This paper presents a model where income distribution and redistributive fiscal policy interact to affect the budget deficit and the pattern of net borrowing of a country. According to the standard representative agent paradigm, a small open economy should smooth consumption by borrowing from (lending to) the rest of the world when its income increases (declines) over time. The simple model of this paper delivers exactly the same predictions in the absence of income dispersion. When income distribution is not degenerate, however, the same model gives rise to a surprising wealth of results. In particular, poor economies with high inequality may exhibit completely counter-intuitive patterns of fiscal policy and external borrowing. The country's production path declines over time, because the more mobile agents leave the country to escape taxation; yet, the country might end up having a budget deficit and borrowing from abroad, thereby reinforcing rather than smoothing the asymmetry in consumption between the two periods. An important feature of this outcome is that it is backed by both the poor and the rich, who gain from the fiscal system at the expense of the middle class.